Taxonomic status of genera Nodularia, Middendorffinaia and Inversiunio (Bivalvia: Unionidae) from South-East Asia: morphometric, genetic and GenBank data. Issue 1 (17th November 2020) - Sayenko, Elena M.; Soroka, Marianna; Akiyama, Yoshihiro B.; Uechi, Takeru; Ito, Kengo; Kondo, Mio
Abstract : Recent investigations of East Asian freshwater mussel genera Nodularia, Middendorffinaia and Inversiunio confirmed validity of the taxa, while their composition and taxonomic uncertainty concerning classification of these genera within a specific subfamily are still in question. The aim of the present study is to clarify the taxonomy and systematics of Nodularia and Middendorffinaia genera from the Russian Far East and Inversiunio from Japan, using a multiple dataset approach that combines morphology of glochidia, detailed conchological analyses with morphometry of adult and glochidial shells, and a molecular technique involving COI barcoding marker. As a result, three genetically distinct and highly divergent lineages were recognized confirming the existence of three distinct genera. The existence of five Nodularia species in Southeast Asia is shown. One of the sequences is shown to be incorrectly assigned to N. jourdyi, while in fact it also represents N. douglasiae, according to the BIN system. Existence of a single Nodularia species, namely N. douglasiae, and a single Middendorffinaia species, namely M. mongolica, in the Russian Far East is supported. We conclude that so-called comparatory species Nodularia amurensis, N. schrencki, and N. vladivostokensis are junior synonyms of the species Nodularia douglasiae ; the comparatory species Middendorffinaia ussuriensis and M. dulkeitiana are junior synonyms of the species Middendorffinaia mongolica . Within Inversiunio specimens from Japan four species were recognized based on types of glochidial microsculpture of shells and genetic data. Gene sequences of Inversiunio verrucosus, endemic to the Seomjingang River basin in South Korea, and I. yanagawensis from Kyushu Island in Japan are very similar and they can be regarded as the same species, with Inversiunio verrucosus as a junior synonym of Inversiunio yanagawensis . Mussels from Honshu Island first referred to I. yanagawensis are shown to be a separate species.